2018
DOI: 10.1039/c8cy00679b
|View full text |Cite
|
Sign up to set email alerts
|

Valorisation of xylose to lactic acid on morphology-controlled ZnO catalysts

Abstract: The activity of ZnO catalysts is significantly driven by the strength of the basic sites determined by their morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 47 publications
3
17
0
Order By: Relevance
“…Not only does it add value to biodiesel production chain, but it also opens the way to exploit waste lignocellulose monosaccharides (pentoses and hexoses). In fact, trioses are found as intermediates during the chemocatalytic conversion of pentoses and hexoses to lactic acid via retro‐aldol condensation reactions (Scheme ) . Therefore, understanding their conversion process also aids to widen alternative green routes to lactic acid production, especially as concerning material supply.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only does it add value to biodiesel production chain, but it also opens the way to exploit waste lignocellulose monosaccharides (pentoses and hexoses). In fact, trioses are found as intermediates during the chemocatalytic conversion of pentoses and hexoses to lactic acid via retro‐aldol condensation reactions (Scheme ) . Therefore, understanding their conversion process also aids to widen alternative green routes to lactic acid production, especially as concerning material supply.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, trioses are found as intermediates during the chemocatalytic conversion of pentoses and hexoses to lactic acid via retro-aldol condensation reactions (Scheme 1). [36][37][38][39][40][41][42] Therefore, understanding their conversion process also aids to widen alternative green routes to lactic acid production, especially as concerning material supply.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the cleavage of the C1−C2 bond can generate FA, while the cleavage of the C2−C3 bond usually yields GcA. Nevertheless, the generation of FA and GcA as byproducts would result in low selectivity to LaA 51,52. Thus, it seems that controlling the selective cleavage of the C3−C4 bond of fructose plays a crucial role in enhancing the selectivity to LaA.…”
mentioning
confidence: 99%
“…Previous reports have identified that basic sites such as O 2− are also reaction sites for this reaction [19] . To investigate the basicity of MOF‐808‐2F, we carried out in situ DRIFTS of adsorbed CO 2 (Figure S13).…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have identified that basic sites such as O 2À are also reaction sites for this reaction. [19] To investigate the basicity of MOF-808-2F, we carried out in situ DRIFTS of adsorbed CO 2 (Figure S13). We only find the hydroxy groups in MOF-808-2F interacting with the CO 2 probe molecules suggesting that the reaction sites identified in this work differ from the previous work.…”
Section: Determination Of Acid Sites Using In Situ Drifts Of Adsorbed...mentioning
confidence: 99%